(untitled) (Future Cities and Environment, 2025)
Many cities are currently rethinking their urban planning with the aim of prioritizing proximity between places of residence and essential services. This approach, promoted mainly in European countries under the concept of the “15-minute city,” seeks to minimize travel times through the use of active modes of transport, such as walking and cycling. To achieve this, a balanced redistribution of urban services is proposed, harmonizing land use with improvements in active transportation infrastructure. However, in Latin America, urban development continues to favor fragmentation, with growth that relies on long commutes and encourages reliance on private vehicles, undermining public transport systems and limiting access to sustainable modes. This study evaluates pedestrian accessibility in the city of Manizales (Colombia), applying a cumulative opportunities potential (COP) model for six types of facilities. The results show a concentration of services in central areas and a marked spatial inequality affecting urban peripheries. To reduce the socio-spatial gap and improve the quality of life, it is suggested to promote proximity policies that improve the distribution of opportunities and strengthen walking access for all inhabitants.